Migration, Remittances, and Household Economic Well-Being in Palungtar Municipality - Devkota, Bijaya Mani (Journal of Development and Administrative Studies, 2025)
This study aims to investigate the connection of migration, remittances, and household economic well-being. This study, a cross-sectional survey of households was used and primary data were collected by conducting a survey of Ward No. 5 of Palungtar Municipality in 2025. Systematic random sampling was used to sample 185 households out of 1,415 households. The household was the unit of analysis, and the information was obtained among the adult respondents. The economic well-being was gauged on a compound index that used income, consumption, and asset indicators. The robust standard errors were used to apply multivariate regression analyses. The findings indicate that there is prevailing social-economic heterogeneity in households. Migrant families that did not receive remittances had less economic wellbeing compared to those who received remittances, although the latter showed much better well-being. An increased dependency ratio decreased the welfare of the households. The acceptance of remittances was higher where there was higher education of the household head and decreased with size of landholdings. In general, the benefits of migration to welfare depended on the remittance flows. Migration does not necessarily imply the improvement of the household welfare whereas remittances are vital in increasing the economic welfare. The policies must enhance financial inclusion, productive use of remittances and social protection of migrant families.